2022
DOI: 10.1186/s12893-022-01494-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of transanal endoscopic microsurgery for the treatment of rectal neuroendocrine tumors

Abstract: Background Transanal endoscopic microsurgery (TEM) has been accepted worldwide for the treatment of local rectal lesions. We aimed to assess the efficacy and safety of TEM in the treatment of rectal neuroendocrine tumors (RNET). Methods A retrospective study of patients who had undergone TEM for RNET at our institution between December 2006 and June 2019 was performed. Demographic and tumor characteristics, operative and pathological details, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Below the size of 1 cm an experienced endoscopist will be able to determine whether it is likely that an R0 resection can be achieved, and then it is reasonable to use at least a lifting or a cap technique to remove the lesion. 52 A meta-analysis showed that ESD was successful for rectal NEN with a complete resection rate of 89%, 4% adverse events and <1% local recurrence. The complete resection rate was better for ESD than for conventional EMR (89 vs. 75%, p < .001).…”
Section: Abdominoperineal Resection (Apr) With Tmementioning
confidence: 99%
See 1 more Smart Citation
“…Below the size of 1 cm an experienced endoscopist will be able to determine whether it is likely that an R0 resection can be achieved, and then it is reasonable to use at least a lifting or a cap technique to remove the lesion. 52 A meta-analysis showed that ESD was successful for rectal NEN with a complete resection rate of 89%, 4% adverse events and <1% local recurrence. The complete resection rate was better for ESD than for conventional EMR (89 vs. 75%, p < .001).…”
Section: Abdominoperineal Resection (Apr) With Tmementioning
confidence: 99%
“…The doughnut appearance commonly occurs when the lesion reaches 1 cm. Below the size of 1 cm an experienced endoscopist will be able to determine whether it is likely that an R0 resection can be achieved, and then it is reasonable to use at least a lifting or a cap technique to remove the lesion 52 …”
Section: Introductionmentioning
confidence: 99%
“…The advantage is that full-thickness resection is possible, and safe surgical outcomes have been reported, including in those with large tumor diameters. [82,83] Although there are few studies comparing between transanal surgery and endoscopic treatment, retrospective studies have shown that ESD and endoscopic full-thickness resection are associated with fewer adverse events and shorter operating time and hospital stay than is transanal surgery for tumors measuring ≤10 mm. [84,85]…”
Section: Local Excisionmentioning
confidence: 99%